Streptococcus agalactiae Causing Neonatal Infections in Portugal (2005–2015): Diversification and Emergence of a CC17/PI-2b Multidrug Resistant Sublineage - Martins, Elisabete R.; Pedroso-Roussado, Cristiano; Melo-Cristino, José; Ramirez, Mário; , The Portuguese Group for the Study of Streptococcal Infections; Oliveira, Henrique; Vaz, Teresa; Gião, Marília; Ferreira, Rui; Silva, Ana Cristina; Costa, Hermínia; Silva, Maria Fátima; et al. (Frontiers in Microbiology, 2017)
The molecular characterization of 218 GBS isolates recovered from neonatal invasive infections in Portugal in 2005-2015 revealed the existence of a small number of genetically distinct lineages that were present over a significant time-span. Serotypes III and Ia were dominant in the population, together accounting for >80% of the isolates. Clonal complex 17 included 50% of all isolates, highlighting the importance of the hypervirulent genetic lineage represented by serotype III ST17/rib/PI-1+PI-2b. Serotype Ia was represented mainly by ST23, previously reported as dominant among invasive disease in non-pregnant adults in Portugal, but also by ST24, showing an increased frequency among late-onset disease. Overall erythromycin resistance was 16%, increasing during the study period (p<0.001). Macrolide resistance was overrepresented among CC1 and CC19 isolates (p<0.001 and p=0.008, respectively). While representatives of the hypervirulent CC17 lineage were mostly susceptible to macrolides, we identified for the first time in Europe a recently emerging sublineage characterized by the loss of PI-1 (CC17/PI-2b), simultaneously resistant to macrolides, lincosamides and tetracycline, also exhibiting high-level resistance to streptomycin and kanamycin. The stability and dominance of CC17 among neonatal invasive infections in the past decades indicates that it is extremely well adapted to its niche; however emerging resistance in this genetic background may have significant implications for the prevention and management of GBS disease.